Characterization of older adults with cancer seeking acute emergency department care: A prospective observational study. Issue 7 (September 2022) - Bischof, Jason J.; Elsaid, Mohamed I.; Bridges, John F.P.; Rosko, Ashley E.; Presley, Carolyn J.; Abar, Beau; Adler, David; Bastani, Aveh; Baugh, Christopher W.; Bernstein, Steven L.; Coyne, Christopher J.; Durham, Danielle D.; et al.
Abstract: Introduction: Disparities in care of older adults in cancer treatment trials and emergency department (ED) use exist. This report provides a baseline description of older adults ≥65 years old who present to the ED with active cancer. Materials and methods: Planned secondary analysis of the Comprehensive Oncologic Emergencies Research Network observational ED cohort study sponsored by the National Cancer Institute. Of 1564 eligible adults with active cancer, 1075 patients were prospectively enrolled, of which 505 were ≥ 65 years old. We recruited this convenience sample from eighteen participating sites across the United States between February 1, 2016 and January 30, 2017. Results: Compared to cancer patients younger than 65 years of age, older adults were more likely to be transported to the ED by emergency medical services, have a higher Charlson Comorbidity Index score, and be admitted despite no significant difference in acuity as measured by the Emergency Severity Index. Despite the higher admission rate, no significant difference was noted in hospitalization length of stay, 30-day mortality, ED revisit or hospital admission within 30 days after the index visit. Three of the top five ED diagnoses for older adults were symptom-related (fever of other and unknown origin, abdominal and pelvic pain, and pain in throat and chest). Despite this, older adults were less likely to report symptoms and less likely to receive symptomatic treatment for pain and nausea than the younger comparison group. Both younger and older adults reported a higher symptom burden on the patient reported Condensed Memorial Symptom Assessment Scale than to ED providers. When treating suspected infection, no differences were noted in regard to administration of antibiotics in the ED, admissions, or length of stay ≤2 days for those receiving ED antibiotics. Discussion: We identified several differences between older (≥65 years old) and younger adults with active cancer seeking emergency care. Older adults frequently presented for symptom-related diagnoses but received fewer symptomatic interventions in the ED suggesting that important opportunities to improve the care of older adults with cancer in the ED exist.